Leading virtual teams : expert solutions to everyday challenges (Boston, Mass. ; London : Harvard Business ; McGraw-Hill, 2010)
How do you lead a team scattered across the globe? How do you keep members you can't see organized, communicative, and productive? This book offers advice on forming virtual teams, assessing their communication and technology needs, and ensuring that they produce high-quality work.
Includes bibliographical references.
BSBA
Keywords: Virtual work teams -- Management